The grindability performance and measurement of surface functional parameter capabilities of difficult-to-machine tool steel under tangential ultrasonic-vibration-assisted dry grinding - Chaudhari A.; Sharma A.; Yusufzai M.Z.K.; Vashista M. (My University, 2025)
The grinding performance of the finished component is significantly affected by the consistency and durability of the grinding mode used in its formation. The current research attempted to evaluate the influence of worktable feed rate and ultrasonic vibration amplitude on grinding outcomes responses such as ground forces, ground surface morphology, surface roughness and topography, surface bearing index, core fluid retention index, grinding temperature, and chip morphology. Experimental works were performed on a setup that was indigenously developed and manufactured. Experiments were conducted on AISI D2 tool steel workpiece material under the tangential ultrasonic-vibration-assisted dry grinding (TUDG), common dry grinding (CDG), and common flood grinding (CFG) modes to compare the effectiveness of each mode in terms of the responses of the grinding outcomes. A comprehensive comparative analysis of each grinding mode is demonstrated, along with observations of changes in the output responses under the effect of the investigated grinding parameters. Findings showed that under identical conditions, the TUDG mode’s surface bearing index and core fluid retention index was higher than that of the CDG and CFG modes. To elucidate these findings. Besides, small, thin chips generated in TUDG mode indicate the ease of grinding of AISI D2 tool steel. © 2023 Taylor & Francis Group, LLC.